2021
DOI: 10.3389/fnagi.2021.599724
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Perivascular Spaces and Cerebral Blood Flow, Brain Volume, and Cardiovascular Risk

Abstract: Background: Basal ganglia perivascular spaces are associated with cognitive decline and cardiovascular risk factors. There is a lack of studies on the cardiovascular risk burden of basal ganglia perivascular spaces (BG-PVS) and their relationship with gray matter volume (GMV) and GM cerebral blood flow (CBF) in the aging brain. Here, we investigated these two issues in a large sample of cognitively intact older adults.Methods: A total of 734 volunteers were recruited. MRI was performed with 3.0 T using a pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Liu et al [ 58 ] investigated the relationship between pseudo-continuous ASL CBF and BG ePVS in a healthy sample. They found a negative association between gray matter CBF and BG ePVS, with significant hypoperfusion observed in those with high grade BG ePVS in multiple cortical regions.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al [ 58 ] investigated the relationship between pseudo-continuous ASL CBF and BG ePVS in a healthy sample. They found a negative association between gray matter CBF and BG ePVS, with significant hypoperfusion observed in those with high grade BG ePVS in multiple cortical regions.…”
Section: Resultsmentioning
confidence: 99%
“… 62 Recent arterial spin labelling (ASL) studies have shown that perivascular perfusion alterations are associated with cerebral blood flow in the aging population. 63 Such alterations in blood flow and perfusion can have profound effects on tissue health and integrity. Hetzer et al .…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have focused on the imaging feature and function of PVS and its correlation with clinical disorders. [9][10][11] However, there is no comprehensive study on the composition of cheese sign, ignoring the various lesions more than the PVS.…”
Section: Discussionmentioning
confidence: 99%